Inflammatory response and endothelial dysfunction in the hearts of mice co‐exposed to SO2, NO2, and PM2.5. Issue 12 (28th September 2015) - Zhang, Yingying; Ji, Xiaotong; Ku, Tingting; Sang, Nan
ABSTRACT: SO2, NO2, and PM2.5 are typical air pollutants produced during the combustion of coal. Increasing evidence indicates that air pollution has contributed to the development and progression of heart‐related diseases over the past decades. However, little experimental data and few studies of SO2, NO2, and PM2.5 co‐exposure in animals exist; therefore, the relevant mechanisms underlying this phenomenon are unclear. An important characteristic of air pollution is that co‐exposure persists at a low concentration throughout a lifetime. In the present study, we treated adult mice with SO2, NO2, and PM2.5 at various concentrations (0.5 mg/m 3 SO2, 0.2 mg/m 3 NO2 6 h/d, with intranasal instillation of 1 mg/kg PM2.5 every other day during these exposures; or 3.5 mg/m 3 SO2, 2 mg/m 3 NO2 6 h/d, and 10 mg/kg PM2.5 for 28 d). Blood pressure (BP), heart rate (HR), histopathological damage, and inflammatory and endothelial cytokines in the heart were assessed. The results indicate that co‐exposure caused endothelial dysfunction by elevating endothelin‐1 (ET‐1) expression and repressing the endothelial nitric oxide synthase (eNOS) level as well as stimulating the inflammatory response by increasing the levels of cyclooxygenase‐2 (COX‐2), inducible nitric oxide synthase (iNOS), tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6). Additionally, these alterations were confirmed by histological staining. Furthermore, we observed decreased BP and increased HR after co‐exposure. Our results indicate that co‐exposure to SO2, NO2, and PM2.5 may be a major risk factor for cardiac disease and may induce injury to the hearts of mammals and contribute to heart disease. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1996–2005, 2016.